Determinants of work engagement among teachers in the context of teleworking - Ciprian Obrad; Cristina Circa (Amfiteatru Economic Journal, 2021)
In Romania, the COVID-19 pandemic has interfered with education, besides other areas, since March 2020. Schools and universities shifted from classroom to online teaching, and the education system needed to adapt to the new form of organization. The paper provides a study on how teachers from Romania dealt with professional challenges, as part of a changing education system. The research aimed to analyse the impact of professional changes on teaching in Romania, between March and June 2020 and to identify the main predictors of work engagement, in the context of teleworking. The research was performed on a sample of 400 teachers from Romania, representative for the entire population of teachers from all Romanian forms of education, with a confidence interval of 5% and a confidence level of 95%. We collected data based on scales and indicators that were validated for the Romanian context and proposed a factorial model, tested subsequently with confirmatory factorial analysis (CFA) and structural equation modelling (SEM). The results show that perceived student engagement and motivation are major determinants of work engagement in teaching.
Keywords: C38; I20; 330; work engagement; teleworking; online learning; factorial analysis; structural equation modelling